IDENTIFIKASI BAKTERI POTENSIAL PATOGEN SEBAGAI INDIKATOR PENCEMARAN AIR DI MUARA SUNGAI DELI Identification of Potential Pathogen Bacteria as Indicator of Polluted Water in Deli River Estuary. - Eunike Saron Meliala; Dwi Suryanto; Desrita Desrita (AQUACOASTMARINE, 2015)
Deli River has been used by people for a long time for washing clothes, utensils, bathing and as latrine. The human activity in the estuary of Deli River causes the river polluted with organic and inorganic pollutant and harm microorganism. The type of waste pollution in waters is related to the type and number of microorganism in the water. The urban and rural waste is not only increase the growth of coliform bacteria but also increase the number of other pathogen bacteria. Deli River Estuary has been polluted indicated by total bacteria count in the area is (811 x 105 cfu/ml). This exceeded threshold value determined by the Regulation of Minister of Living Environment (2004). There were 9 species of potential pathogen bacteria identified using API 20 E i.e: Escherichia coli, Klebsiella oxytoca, Klebsiella ornithinolytica, Cedecea lapegei, Aeromonas hydrophyla, Aeromonas sobria, Aeromonas caviae, Ewingella americana and Vibrio fluvialis.Keyword : Deli River, E.coli, Pathogen Bacteria.